Development of a conceptual framework for the management of biodiversity and ecosystem services in the Mexican Caribbean - Sánchez-Quinto, Andrés; Costa, Julliet Correa da; Zamboni, Nadia S.; Sanches, Fábio H. C.; Principe, Silas C.; Viotto, Evangelina V.; Casagranda, Elvira; Veiga-Lima, Francisco A. da; Possamai, Bianca; Faroni-Perez, Larisse (Biota Neotropica, 2020)
Abstract: Coral reefs and mangroves support rich biodiversity and provide ecosystem services that range from food, recreational benefits and coastal protection services, among others. They are one of the most threatened ecosystems by urbanization processes. In this context, we developed a conceptual framework for the management of biodiversity and ecosystem services for these coastal environments. We based our workflow on two sections: “Information base” and “Governance” and use the Puerto Morelos Coastal region as a case study for coastal protection. Puerto Morelos is between two of the most touristic destinations of Mexico (Playa del Carmen and Cancun) that has experienced an increase of population in the past four decades resulting in an intensification of multiple threats to its ecosystems. We characterized the two ecosystems with a “Management Units” strategy. An expert-based ecosystem services matrix was also described in order to connect mangroves and coral reef ecosystems with the multiple beneficiaries. Then an ecosystem model (conceptual model and Global Biodiversity model) was developed. The conceptual model was useful in understanding the interplay processes between systems regarding the ecosystem service of “Coastal Protection”. The Global Biodiversity model evidenced the human-induced shifts in the biodiversity for mangrove and coral reefs ecosystems. Also, a projection for 2035 of “best” and “worst” scenarios was applied using GLOBIO3. A DPSIR conceptual framework was used to analyze environmental problems regarding ecosystem services maintenance. Finally, we evaluated a set of policies associated with these ecosystems that favor coastal protection integrity. This framework facilitates the identification of the most relevant processes and controls about the provision of coastal protection service. It can also be useful to better target management actions and as a tool to identify future management needs to tackle the challenges preventing more effective conservation of coastal environments.